Active microfluidic systems for cell sorting and separation. (March 2020) - Sivaramakrishnan, Muthusaravanan; Kothandan, Ram; Govindarajan, Deenadayalan Karaiyagowder; Meganathan, Yogesan; Kandaswamy, Kumaravel
Abstract: Rapid progress in the field of microfluidics coupled with increase in demand for cell separation techniques for biomedical diagnostics has gained significant attention among researchers. Designing cost-effective and miniaturized microfluidic devices with increased detection accuracy and throughput is a challenging task. Therefore, it is crucial to evaluate the current state-of-the-art microfluidic devices. This article critically reviews four different types of active microfluidic devices such as fluorescence-activated cell sorting, magnetic-activated cell sorting, dielectrophoresis, and acoustic microfluidic devices. Furthermore, their applications and limitations were discussed succinctly from an efficiency standpoint. Graphical abstract: Image 1